1979
DOI: 10.1111/j.1365-2621.1979.tb00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the permeability of chilled meat packaging film under conditions of high humidity

Abstract: Modifications to the American Society for Testing and Materials standard method (D1434) for the determination of film oxygen permeability are described. The method gives results consistent with published data and allows the measurement of permeability under likely food storage humidity conditions. It is recommended that the permeability of hydrophilic materials used for meat packaging should be measured at 100% relative humidity (RH) to permit adequate comparison with other films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…This dose range is approximately equal in microbial effect to commercial fumigation with ethylene oxide (Farkas, 1988). Some studies have reported that irradiation had no effect on packaging materials at doses below 20 kGy (Rigg, 1979;Noomhorm et al, 2003). Data in Table 3 indicate that products containing irradiated spices (irsp) had significantly (P > 0.05) lower microbial numbers in products irradiated (irp) or non-irradiation (nirp) with 2 kGy dose compared with the product containing non-irradiated spices (nirsp).…”
Section: Effect Of C-irradiation On Microbiological Quality Of Lunchementioning
confidence: 97%
“…This dose range is approximately equal in microbial effect to commercial fumigation with ethylene oxide (Farkas, 1988). Some studies have reported that irradiation had no effect on packaging materials at doses below 20 kGy (Rigg, 1979;Noomhorm et al, 2003). Data in Table 3 indicate that products containing irradiated spices (irsp) had significantly (P > 0.05) lower microbial numbers in products irradiated (irp) or non-irradiation (nirp) with 2 kGy dose compared with the product containing non-irradiated spices (nirsp).…”
Section: Effect Of C-irradiation On Microbiological Quality Of Lunchementioning
confidence: 97%
“…The results confirm that the PA/PE film is water-sensitive and that the barrier properties decrease with increased water sorption in the hygroscopic component. [5][6]19 The OTR reference value of the PA/PE film is 35 ml/m 2 /24 h/atm (information from the producer). This value, measured at standard conditions (0/50% RH, 23°C), is considerably lower than our measured value of 51 ml/m 2 /24 h/atm (0/100% RH, 23°C).…”
Section: Pa/pe Lid Filmmentioning
confidence: 99%
“…2 The effect of low relative humidity (less than 50%) is minor, but an exponential increase is observed at higher humidity (over 60-70%). 1,[5][6][7] Dairy products and cured meat products have high water activity (a w ≥ 0.9) 8 and cooling cabinets can normally show a relative humidity around 60-70%. Even though the hygroscopic polymer is commonly protected by a water-barrier material, water permeation into the packaging material during storage of these products is unavoidable 7 and OTR measurements in the range of 60-100% RH are therefore very relevant.…”
Section: Introductionmentioning
confidence: 99%
“…The storage life of vacuum packaged meat is inversely related to the oxygen permeability of the film used for packaging (Newton & Rigg, 1979). Vacuum packaged meats are usually stored at temperatures close to 0°C while the meat exposes the packaging films to conditions of high humidity (Rigg, 1979). Reported oxygen permeabilities of packaging films are usually those measured at ambient temperatures and moderate humidities, but both temperature and humidity can affect the rates at which gases are transmitted through films.…”
Section: Introductionmentioning
confidence: 99%